A user's guide for α‐synuclein biomarker studies in biological fluids: Perianalytical considerations. Issue 8 (22nd July 2017) - Mollenhauer, Brit; Batrla, Richard; El‐Agnaf, Omar; Galasko, Douglas R.; Lashuel, Hilal A.; Merchant, Kalpana M.; Shaw, Lesley M.; Selkoe, Dennis J.; Umek, Robert; Vanderstichele, Hugo; Zetterberg, Henrik; Zhang, Jing; et al.
Abstract: Parkinson's disease biomarkers are needed to increase diagnostic accuracy, to objectively monitor disease progression and to assess therapeutic efficacy as well as target engagement when evaluating novel drug and therapeutic strategies. This article summarizes perianalytical considerations for biomarker studies (based on immunoassays) in Parkinson's disease, with emphasis on quantifying total α‐synuclein protein in biological fluids. Current knowledge and pitfalls are discussed, and selected perianalytical variables are presented systematically, including different temperature of sample collection and types of collection tubes, gradient sampling, the addition of detergent, aliquot volume, the freezing time, and the different thawing methods. We also discuss analytical confounders. We identify gaps in the knowledge and delineate specific areas that require further investigation, such as the need to identify posttranslational modifications of α‐synuclein and antibody‐independent reference methods for quantification, as well as the analysis of potential confounders, such as comorbidities, medication, and phenotypes of Parkinson's disease in larger cohorts. This review could be used as a guideline for future Parkinson's disease biomarker studies and will require regular updating as more information arises in this growing field, including new technical developments as they become available. In addition to reviewing best practices, we also identify the current technical limitations and gaps in the knowledge that should be addressed to enable accurate and quantitative assessment of α‐synuclein levels in the clinical setting. © 2017 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.